1985
DOI: 10.1177/019459988509300206
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Tumors: Preoperative Measurement and Correlation with Postoperative Facial Nerve Function

Abstract: The cases of 67 patients consecutively operated on for acoustic tumors are reported. Preoperative records consist of tumor size and the position of the fourth ventricle on computerized tomography (CT) scans. An analysis is made of the immediate postoperative and current function of the facial nerves. There is a statistically significant relationship between the number of weak or paralyzed seventh nerves and displacement of the fourth ventricle (P less than .05). It is now possible to accurately measure acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…14 Previous studies have demonstrated that the size and staging of the tumor influence postoperative facial nerve outcome. [10][11][12][13][14][15] Our study also confirms that large tumors correlate with poor facial nerve outcome. Similarly, in their series of 129 patients, Lalwani et al 21 describe the facial nerve outcome at 1 year or greater following surgery as being inversely correlated with the size of the tumor (p < 0.02).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…14 Previous studies have demonstrated that the size and staging of the tumor influence postoperative facial nerve outcome. [10][11][12][13][14][15] Our study also confirms that large tumors correlate with poor facial nerve outcome. Similarly, in their series of 129 patients, Lalwani et al 21 describe the facial nerve outcome at 1 year or greater following surgery as being inversely correlated with the size of the tumor (p < 0.02).…”
Section: Discussionsupporting
confidence: 81%
“…These factors include size, volume, staging of the tumor, histological features, clinical presentation, tumor extension, changes in the internal acoustic meatus, radiological features, operative approach, extent of resection, and experience of the surgeon. [10][11][12][13][14][15]17,18 A patient's facial nerve function after VS surgery is one of the major determinants of morbidity and quality of life following the surgery. 19,20 Our study aimed to identify the clinical and radiological factors that can be used to predict the facial nerve outcome after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that there is justification for early excision of acoustic neuromas in order to reduce the mor bidity and mortality and to improve chance of preserving the facial nerve [10] and hearing [11], Although BAEP and MRI have made the diagnosis of CPAT more effi cient, some patients are still presenting with large tumors because CPAT often remain asymptomatic for a long time. In our series, the mean delay between the first and the presenting symptom was 4 years.…”
Section: Discussionmentioning
confidence: 99%